ARD1-mediated Hsp70 acetylation balances stress-induced protein refolding and degradation - Ji Hae Seo (Nature Portfolio, 2016)
The chaperone Hsp70 has a dual role, promoting both protein refolding and protein degradation. Seo and Park et al. show that Hsp70 acetylation enhances protein refolding after stress, and that subsequent deacetylation progressively promotes ubiquitin ligase binding and protein degradation.